Neuroprotective effects of 7-tetrahydroxyflavone against Alzheimer's disease through Hypothalamic-Pituitary-Adrenal Axis and Nrf2 linked bidirectional pathways / Assoc. Prof. Dr. Hanish Singh Jayasingh Chellammal ... [et al.] - Jayasingh Chellammal, Hanish Singh; Hazizul Hasan, Mizaton; Sukumaran, Sathesh Kumar; Zakaria, Yuslina; Husain, Noreen (Faculty of Pharmacy, 2023)
Alzheimer’s disease is an age-related memory loss that affects cognitive function. In Alzheimer’s type of dementia, stress escalates the acetylcholinesterase enzyme with accumulation of amyloid peptide which eventually causes declining cognition, emotion, and social health. Worldwide 46.8 million people are living with dementia and in Malaysia was 123,000 people in 2015 and projected to 261,000 by 2030 and to 590,000 in 2050. National health and morbidity survey-senior health of Malaysia, 2018 states the prevalence is 8.6%. In Malaysia, according to Alzheimer’s disease International, the prevalence of dementia was 123,000 people during 2015. As per Alzheimer’s disease foundation, the number was projected to be 261,000 by 2030 and will continue to increase to 590,000 people in 2050. It’s also denoted that in Malaysia 8.6% of elderly population prevails with dementia with its rapid growth and morbidity, it ranks second on the burden of disease in Asia Pacific Region. Currently, there is a worldwide effort to find better ways to treat the disease, delay its onset, and prevent it from developing.